The Impact of Immunization with Anti-Coronavirus Vaccines on the Incidence of COVID-19 in Employees of a Large Tuberculosis Institution in Moscow - E. M. Bogorodskaya; I. V. Nozdrevatykh; E. L. Khristoforova; E. M. Belilovskiy (Эпидемиология и вакцинопрофилактика)
Relevance. Employees of a TB facility are a high-risk group for the incidence of COVID-19 due to their involvement in the detection and treatment of a new coronavirus infection, so vaccination of staff should play a significant role in their protection against a new coronavirus infection. Aim. Analyze the incidence of COVID-19 in employees of a large TB medical organization in a big city before and after mass immunization with anti-coronavirus vaccines. Materials & Methods. An analysis was made of the incidence of a new coronavirus infection COVID-19 among employees of the Moscow Research and Clinical Center for Tuberculosis Control during April 1, 2020–September 30, 2021, considering two periods of nine months in 2020 (2771 employees) and 2021 (2845 employees) and taking into account the data on the implementation of the first and second vaccinations carried out during the study period. Calculation of the average weekly and annual incidence per 1000 employees was carried out taking into account the different time spent by employees "at risk of getting sick". The incidence rate was calculated both for the entire study period as a whole and for weeks of high risk of COVID-19 incidence in the population of Moscow with an indicator of 500 or more per 100,000 population. Results. A comparative analysis of the incidence of COVID-19, registered from April 1, 2020 to October 1, 2021, was carried out among the average number of 2808 employees of the leading anti-TB institution in Moscow, taking into account vaccination. During the period under review, a total of 35.5% of employees in the institution fell ill and the annual incidence of staff was 177.4 per 1000 employees. 5.7% [95% CI 4.4–7.4%] of previously ill employees had a recurrence of the disease. Being unvaccinated until September 2020 and limitedly vaccinated until July 2021, the staff of the Center was massively immunized from July to August 2021 – up to 86.0% of the institution's staff by the end of the observation period. Based on the calculation of the weekly number of disease cases and of not yet ill persons among fully vaccinated, vaccinated with one drug, not vaccinated and previously ill, the incidence in these groups was compared, taking into account the time at risk of disease before a new case of COVID-19 was registered. For periods of high monthly incidence of the city's population (above 500 per 100 thousand), the annual notification rate of the unvaccinated was 2.8 times higher than that of the fully vaccinated (408.2 and 144.0 per 1000 people, RR = 2.8 [95% CI: 2.0–4.0]). The notification rate among those vaccinated with only one component of the two-component vaccine was 1.5 times higher than among those who were not vaccinated (271.5 and 409.2 per 1000 people. RR = 1.5 [95% CI: 1.04–2.2]). The probability of getting sick in fully vaccinated people was significantly higher than in those who previous infected with SARS-CoV-2 (144.0 and 78.0 per 1000 people, RR = 1.9 [95% CI: 1.1–3.1]). Conclusions. The obvious effectiveness of vaccination has been confirmed, including among the personnel of medical organizations directly involved in the fight against a new coronavirus infection.